Character Education with Setara Daring Application in Non-Formal Education - Wica, Pratama Yoga; Marzuki, Marzuki (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Character is always a problem in human life that must be overcome immediately. One of the alternatives offered to build human character is through character education in non-formal schools. The school has an application that is able to help the character education process which is named the online equivalent application. This application is a learning system designed by the Ministry of Education and Culture Republic Indonesia. This research is in the form of a qualitative description and the purpose of this study is to describe the function of Setara daring applications in fostering the character of learning citizens. Data collection techniques using observation, interviews and documentation. The data collection instruments used were observation sheets, interview guidelines and document review. The data analysis technique used in this study is interactive model of analysis. The results of the application of the Setara Daring application turned out to have a major impact on the character education of learning citizens especially on the character of discipline, responsibility, independence, and caring for others.